1992
DOI: 10.1002/syn.890120303
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the nigrotectal and nigrothalamic pathways in kappa opioid‐induced circling

Abstract: The relationship between kappa opioid-induced movement and output stations of the substantia nigra pars reticulata (SNpr) was examined using the rodent circling model. Contralateral rotation produced by intranigral microinjection of the kappa opiate U50,488 was lower in animals with ibotenic acid lesions of either the ipsilateral ventromedial thalamus or superior colliculus than in control animals without lesions. These results suggest that endogenous kappa opioids in the SNpr may influence movement through ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Consistent with the latter idea, a number of laboratories have reported that unilateral microinjections of U-50,488 or prodynorphin peptides into the substantia nigra pars reticulata cause contralateral circling in the adult rat (Friederich, Friederich, & Walker, 1987;Herrera-Marschitz et al, 1986;Matsumoto, Brinsfield, Patrick, & Walker, 1988;Morelli & Di Chiara, 1985;Thompson & Walker, 1992). This enhanced motor movement is not dependent on dopaminergic nigrostriatal connections, rather -opioid receptor stimulation directly modulates GABAergic output neurons in the nigrotectal and nigrothalamic pathways (Herrera-Marschitz et al, 1986;Matsumoto et al, 1988;Morelli & Di Chiara, 1985;Thompson & Walker, 1992).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Consistent with the latter idea, a number of laboratories have reported that unilateral microinjections of U-50,488 or prodynorphin peptides into the substantia nigra pars reticulata cause contralateral circling in the adult rat (Friederich, Friederich, & Walker, 1987;Herrera-Marschitz et al, 1986;Matsumoto, Brinsfield, Patrick, & Walker, 1988;Morelli & Di Chiara, 1985;Thompson & Walker, 1992). This enhanced motor movement is not dependent on dopaminergic nigrostriatal connections, rather -opioid receptor stimulation directly modulates GABAergic output neurons in the nigrotectal and nigrothalamic pathways (Herrera-Marschitz et al, 1986;Matsumoto et al, 1988;Morelli & Di Chiara, 1985;Thompson & Walker, 1992).…”
Section: Discussionmentioning
confidence: 73%
“…This enhanced motor movement is not dependent on dopaminergic nigrostriatal connections, rather -opioid receptor stimulation directly modulates GABAergic output neurons in the nigrotectal and nigrothalamic pathways (Herrera-Marschitz et al, 1986;Matsumoto et al, 1988;Morelli & Di Chiara, 1985;Thompson & Walker, 1992). Systemic injections of U-50,488 may increase the locomotor activity of preweanling rats by affecting these same nondopaminergic pathways.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, reducing endogenous DA stores with AMPT did not eliminate the locomotor activating effects of kappa opioid receptor stimulation. This finding indicates that: (a) U-50,488 increases the locomotor activity of preweanling rats through a non-dopaminergic mechanism (see Matsumoto et al 1988;Thompson and Walker 1992); and (b) quinpirole and NPA attenuate U-50,488-induced locomotor activity by stimulating postsynaptic DA receptors. Consistent with this conclusion, quinpirole blocked the U-50,488-induced locomotor activity of both AMPT-and vehicle-pretreated rats.…”
Section: Experiments 4 Effects Of Ampt and Quinpirole On U-50488-indmentioning
confidence: 88%
“…For example, microinjecting U50,488 or dynorphin (the endogenous ligand for κ-opioid receptors) into the substantia nigra pars reticulata (SNR) induces contralateral rotation in adult rats (in a unilateral preparation), while stimulating forward locomotion in preweanling rats (Herrera-Marschitz et al, 1984, 1986; Morelli and Di Chiara, 1985; Matsumoto et al, 1988; Thompson and Walker, 1992; Collins et al, 2000). For this reason it is surprising that systemic administration of a κ-opioid receptor agonist has nearly opposite effects on the motoric responsiveness of preweanling and adult rats.…”
Section: Discussionmentioning
confidence: 99%